2012
DOI: 10.1111/cid.12019
|View full text |Cite
|
Sign up to set email alerts
|

Deviations between Placed and Planned Implant Positions: An Accuracy Pilot Study of Skeletally Supported Stereolithographic Surgical Templates

Abstract: As slight deviations between planned and placed implants especially may occur even with skeletal-supported templates, the clinician should be aware not to overestimate advocated surgical safety by using static navigation tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
3
28
2
Order By: Relevance
“…As of all tip and shoulder deviation in both BL and MD directions, only for the shoulder deviation in BL direction a slightly statistical significant difference was found for the use of fixation pins. This means that this study is consistent with the authors' accuracy study on the placement of two or four implants in the edentulous maxilla . It was found that fixation pins provide no additional stability to the surgical template and therefore do not result in a more accurate transfer from implant planning to implant placement.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As of all tip and shoulder deviation in both BL and MD directions, only for the shoulder deviation in BL direction a slightly statistical significant difference was found for the use of fixation pins. This means that this study is consistent with the authors' accuracy study on the placement of two or four implants in the edentulous maxilla . It was found that fixation pins provide no additional stability to the surgical template and therefore do not result in a more accurate transfer from implant planning to implant placement.…”
Section: Discussionsupporting
confidence: 89%
“…Koop and colleagues and Van Assche and Quirynen notice that a parallel and central positioning of the drill guide is crucial. However, a limited mouth opening might cause the drill head to be inclined more mesial or palatinal …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses showed the use of the real‐time surgical navigation system for the placement of different lengths of implants or locations that had similar accuracies, which was inconsistent with the use of surgical templates. The deviations appeared to be greater when implants were placed in distal locations or when long implants were placed . Our results indicate that use of a real‐time surgical navigation system minimizes the planned‐placed deviations and provides higher stabilities when placing more than one zygomatic implant, irrespective of the lengths of implants or the placed locations of implants.…”
Section: Discussionmentioning
confidence: 70%
“…The deviations appeared to be greater when implants were placed in distal locations or when long implants were placed. 37,38 Our results indicate that use of a real-time surgical navigation system minimizes the planned-placed deviations and provides higher stabilities when placing more than one zygomatic implant, irrespective of the lengths of implants or the placed locations of implants. These advantages may help minimize the risk of complications and ensure anchorage for better support of the prosthesis.…”
Section: Discussionmentioning
confidence: 74%